REINTERPRETASI KONSEP PUNISHMENT BAGI PESERTA DIDIK DALAM HADIS PENDIDIKAN ṢALAT - Prastio Prastio (Asaatidzah, 2022)
Rasulullah was a gentle and loving person. Meanwhile in one of the hadiths there is a "contradictory" teaching as if legalizing acts of violence against children if only understood textually. Therefore, a study is needed that aims to reinterpret so that the values of primacy that he teaches are not distorted by non-contextual understanding. This research is a library research, the primary source is H.R. Abu Daud was studied using Abdullah Saeed's contextual interpretation method which is divided into four stages: 1) Encounter with the world of the text; 2) Critical analysis; 3) Meaning for the first recipients; dan 4) Meaning for the present. The results showed that the hadith about the command to educate children to pray is universally applicable. Meanwhile, the matan which contains the command to hit a child who is not alat is casuistic in nature for the context of Arab society in the past. That the word "hit" implies that there must be punishment for children who leave tools. Then it is contextualized in various stages that according to the child's condition and still pays attention to the child protection act. The method of tarhīb or scaring the child leaving ṣalat can be an option.